Chloride Homeostasis in Neurons With Special Emphasis on the Olivocerebellar System: Differential Roles for Transporters and Channels - Rahmati, Negah; Hoebeek, Freek E.; Peter, Saša; De Zeeuw, Chris I. (Frontiers in Cellular Neuroscience, 2018)
The intraneuronal ionic composition is an important determinant of brain functioning. There is growing evidence that aberrant homeostasis of the intracellular concentration of Cl- ([Cl-]i) evokes, in addition to that of Na+ and Ca2+, robust impairments of neuronal excitability and neurotransmission and thereby neurological conditions. More specifically, understanding the mechanisms underlying regulation of [Cl-]i is crucial for deciphering the variability in GABAergic and glycinergic signaling of neurons, in both health and disease. The homeostatic level of [Cl-]i is determined by various regulatory mechanisms, including those mediated by plasma membrane Cl- channels and transporters. This review focuses on the latest advances in identification, regulation and characterization of Cl- channels and transporters that modulate neuronal excitability and cell volume. By putting special emphasis on neurons of the olivocerebellar system, we establish that Cl- channels and transporters play an indispensable role in determining their [Cl-]i and thereby their function in sensorimotor coordination.